Causativization in Arabic: Evidence for the interface between semantics and morpho-phonology - Teimi, Cherif (International Journal of Language and Literary Studies, 2022)
Meaning is derived through the interaction of the components of the linguistic system. As established within the Parallel Architecture Framework (Jackendoff 1997), the linguistic system is composed of components considered equal in terms of producing meaning. In other words, linguistic components are related to each other via interface rules and principles so that they cooperate to derive meaning. In this regard, Morpho-phonological processes constitute the interface between morpho-phonology and semantics. Morphological and phonological features of a word bear on its semantic interpretation. In this article, I deal with Causativization in Modern Standard Arabic (MSA, henceforth), representing a pure phenomenon for the morpho-phonology-semantics interface. Causative verbs in MSA provide good insights into this issue. Adopting Jackendoff’s Conceptual Semantics framework proves that morphology is an autonomous generative component that can generate some aspects of meaning either independently or in cooperation with phonology and/ or other linguistic components; therefore, this proves the interface between morpho-phonology and semantics.